Can vitamin D deficiency affect the development of cancer? - review of the literature - Różańska-Smuszkiewicz, Gabriela; Koszyczarek, Karolina; Kotowska, Maja; Zamirska, Wiktoria; Ziemiański, Albin; Zięba, Katarzyna; Zygmunt, Anna; Smuszkiewicz-Różański, Paweł (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Over recent years, there has been a noticeable increase in cases of cancer around the world. At the same time, there is the problem of vitamin D deficiency, which may affect up to one-quarter of the population. The aim of this article is to link these two epidemics and organize knowledge about vitamin D and its multidirectional effects related to many diseases, especially cancer. State of knowledge: Many scientific works have proven that vitamin D has a beneficial effect not only on the known calcium-phosphate metabolism. Researchers emphasize its pleiotropic effect on many organs and systems in the human body, and thus on many diseases, including cancer. Studies show that vitamin D modulates the expression of many different miRNAs specific to various types of cancer. The results of in vitro and in vivo studies showed the effect of calcitriol on cell growth and development. It influences processes such as differentiation, proliferation, apoptosis, strengthens the immune system, and reduces oxidative stress. Summary: Based on accumulated research, we can conclude that vitamin D presumably regulates the entire process of tumorigenesis, from initiation to metastasis and cell-microenvironment interactions. However, some studies do not confirm these data or provide contradictory results. For this reason, it is necessary to deepen research on this topic in order to establish specific recommendations, therapeutic and preventive plans. However, vitamin D and its role in the pathogenesis of many diseases should not be underestimated. In cases of low vitamin D concentration in the body, its supplementation will be reasonable, considering the functional identity of this source compared to sun exposure or diet.